What affects bank debt rejections? Bank lending conditions for UK SMEs. Issue 6 (13th April 2021) - Sun, Mingchen; Calabrese, Raffaella; Girardone, Claudia
Abstract : Using the UK SMEs Finance Monitor data over 2011–2017, we explore the determinants of bank debt rejections for UK SMEs. In the wake of the global financial crisis, business overdrafts and term loans show slightly different trends although the factors affecting rejections are similar. We find that since 2014 rejection rates reduced for both facilities and they remained stable in the run-up to the Brexit referendum and its immediate aftermath, although export and import SMEs operating in industries with a high share of EU trade experienced tighter conditions. Further, we present robust evidence that firms with female owners, organised in partnerships, and with a higher initial credit balance are more likely to have their credit application approved. Finally, younger, smaller and more innovative SMEs are more likely to be rejected, while their chance of being successful in their credit applications increases substantially after 2014.